Kinematic links between subduction along the Hellenic trench and extension in the Gulf of Corinth, Greece: A multidisciplinary analysis - Vassilakis, E; Royden, L.; Papanikolaou, D. (Earth and Planetary Science Letters, 2011)
Rapid northeast-vergent subduction along the Hellenic trench, at ~ 35 mm/yr, exists in concert with widespread extensional and strike-slip faulting within the upper plate lithosphere of western Greece. Integration of regional geomorphic, geologic, seismic, GPS, remote sensing and field data demonstrates that young and active deformation in the area, extending from the Hellenic subduction boundary near Kephalonia to the Gulf of Corinth, consists of an interconnected network containing highly localized zones of deformation. These bound a series of crustal fragments with relatively little internal deformation. These deformation zones merge to form triple junction-like features at the western end of the Gulf of Corinth and in the Amvrakikos Gulf. At the western end of the Corinth Gulf, most of its 14 ± 2 mm/yr of extension is relayed to the northwest along a prominent zone of left-slip and extension through Lake Trichonis and the Amphilochia fault zone (11 ± 2 mm/yr). The remaining displacement across the western Gulf of Corinth is relayed into 7 ± 2 mm/yr of right-slip on the southwest-striking Achaia fault zone, which traverses the northwestern margin of the Peloponnesus. A second triple-junction like feature occurs in the Amvrakikos Basin, where the left-slip Amphilochia fault zone, the right-slip Kephalonia transform fault (15 ± 2 mm/yr) and the convergent thrust front of northern Hellenides (4 ± 2 mm/yr) are joined. Thus the extensional deformation in the Gulf of Corinth can be shown to be connected to convergence and subduction along the Hellenic trench through a series of discrete deformation zones that are not dissimilar from those observed in the global plate tectonic system.
Keywords: GPS; Gulf of Amvrakikos; Gulf of Corinth; Hellenic trench; Kephalonia transform; remote sensing